REPRESENTATION OF THE REALITY IN THE FIRST GEORGIAN DOCUMENTARY FILMS - Lia Zambakhidze; Nino Chalaganidze (International Journal of Innovative Technologies in Social Science, 2024)
History of the Georgian cinema counts more than hundred years. In the beginning of the XX century several projecting halls had already started operation in Georgia. The local society upon appearance of the film making, in 1896, shared new directions of the art and if we will take a glance on dynamics of development, we can say boldly it got rather interested in it. During a definite period of time opportunities and impacts of new means of the mass communication became a subject of interests not only of authors, but public persons (actors) as well. The work over creation of the national film making was started. For the purpose of encouraging of patriotic moods, broadening of education and rising awareness among viewers, directors, writers and aristocracy of that period consolidated. It was just an attempt. After occupation happened in 1921 Georgian film making, as well as other fields of the art found themselves in the Soviet propagandistic pliers. The target of this thesis (work) is to represent dynamics of development of the Georgian film making, to analyze the cadres kept in the Georgian National Archive from the beginning of the XX century – till the occupation of 1921, to demonstrate the key features of the documentary film developed according to the political, social or economic processes and global trends, authors’ achievements in the process of translation of the idea from the creative viewpoint.